Penyuluhan Pengelolaan Keuangan Keluarga Pada Ibu Rumah Tangga Di Kelurahan Sei Agul - Dita Maulia Ahmad; Muhammad Irfan Nasution (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This community service is carried out in the 12 Gg. Madrasah Sei Agul village, District of West Medan. This community service aims to provide knowledge to the community about the importance of managing household finances. With the bookkeeping of the recording of receipts and expenditures, expenditures will be more orderly and directed. The method used in this community service is the training method. Training is a method used to improve knowledge, skills and change participants' attitudes in a specific way. In this training method, the author will teach directly by providing understanding in managing household finances by giving examples and explaining household financial statements. In general, the target community has never made a record of their household finances. The results obtained from this Real Work Lecture are increased knowledge about financial management for housewives. This is done to ensure the appropriateness of the budget within each household, in the household financial management process